Neglecting Transparency in the Qur'an Recitation Test for Legislative Candidates in Aceh - Karim, Zahlul Pasha; Muazzinah, Muazzinah; Bantasyam, Saifuddin; Efendi, Sumardi (Universitas Lampung, 2024)
This research examines the neglect of the principle of transparency in Qur'an literacy tests for legislative candidates in Aceh, which has hindered voters from making informed decisions. It explores two key questions: What forms does the neglect of transparency take in the Qur'an literacy test for legislative candidates in Aceh? And what are the causes and impacts of this neglect? The findings reveal that the neglect of transparency occurs in two primary forms: first, the establishment of subjective score standards, and second, the refusal of the Independent Electoral Commission (KIP) Aceh to publicly announce the test results. This issue arises from the absence of regulatory mechanisms that would require KIP Aceh to disclose the test outcomes and from the closed process by which the score standards are determined in collaboration with the Qur'an Reading Test Team. The impact of this neglect is the limited public access to vital information needed to elect legislators with religious competence, a quality of significant importance in Aceh, where religious knowledge plays a key role in qualifying individuals for public office.